Trends in Climate Change Education Studies in the Last Ten Years: A Systematic Literature Review - Hadiapurwa, Angga; Ali, Mohammad; Ropo, Eero; Hernawan, Asep Herry (Universitas Pendidikan Ganesha, 2024)
Climate change is a concern for all countries in the world. UNESCO is taking part in efforts to increase awareness regarding climate change, one of which is by creating the Greening Education Partnership program. Climate Change Education (CCE) is an effort in the education sector to increase students' awareness of climate change. This article attempts to analyze publication trends regarding CCE and explore other opportunities for further research on the topic of CCE. The method used is the systematic literature review (SLR) method and data analysis using bibliometrics. The data used in this research are documents published by journals on the Scopus database published in 2013-2022. In 2013-2022, 462 documents can be searched in the Scopus database with the keyword ‘climate change education’. The analysis results show that discussions about CCE related to curriculum, learning, and students have been widely studied and published. However, there is no visible academic interaction between the authors. These conditions can be the basis that CCE needs to be implemented thoughtfully to increase awareness of environmental change. Apart from that, its implementation also requires collaborative roles from each sector so that CCE implementation can be carried out optimally. There needs to be a policy to encourage implementation by integrating CCE and the curriculum. Schools and universities encourage teachers and lecturers to deliver CCE in learning by including specific topics that can be related.